Immunological abnormalities in haemophilia: are they caused by American factor VIII concentrate?. Issue 6399 (15th October 1983) - Froebel, K S; Madhok, R; Forbes, C D; Lennie, S E; Lowe, G D; Sturrock, R D
Abstract : Scottish patients with haemophilia, most of whom had received no American factor VIII concentrate for over two years, were found to have immunological abnormalities similar to those in their American counterparts--that is, a reduced proportion of T helper cells, an increased proportion of T suppressor cells, and a reduced response to concanavilin A. Factor VIII from both the United States and Scotland severely inhibited the in vitro lymphocyte response to mitogens in patients and controls. The American and Scottish concentrates could not be distinguished in terms of either patient usage or their effect in vitro. These results argue against a disease vector specific to American blood products.